A mixed-methods study to identify key priorities around improving team-based care coordination for patients receiving combination IV and oral systemic anti-cancer therapy. Issue 28 (1st October 2022) - Hanna, Kirollos Samir; Plotkin, Elana; Page, Ray D.; Kottschade, Lisa A.; Baldwin, Billie; Raymond, Martha; Anderson, Mary; Oubre, Kathy; Wood, Laura S.; Kim, Joseph; Boehmer, Leigh
Abstract : 52 Background: When combination medical therapy incorporates both IV and oral anti-cancer agents, patients may experience compound side effects and face challenges with treatment adherence. To assess how community cancer programs may improve care coordination for patients receiving combination IV/oral systemic therapy, the Association of Community Cancer Centers (ACCC) conducted a mixed-methods study that involved healthcare professionals (HCPs), patients and caregivers. Methods: The study followed a sequential quantitative-qualitative design to answer questions around the barriers or challenges associated with combination IV/oral systemic therapy. The quantitative phase included an online survey of HCPs (by ACCC) and a survey of patients and caregivers (by Edge Research, in collaboration with several patient advocacy organizations). In the quantitative phase, the survey results were contextualized through two HCP focus groups and individual HCP interviews. Results: Comparing and contrasting the patient survey (n = 113) and HCP survey (n = 157) results revealed insights around the following themes: Top Challenges: Patients felt their top challenges were side effects (57.5%); inconvenience going to medical appointments (37.2%); and financial burden (36.3%). HCPs perceived top challenges as cost of care to the patient (24.0%); coordination and delivery of oral agents (22.1%); and health insurance coverage (21.9%). In focus groups, HCPs explained how they were investing significant staffing resources to prevent and mitigate financial toxicity, especially for patients receiving oral therapies. Methods of Communication: 35.4% of patients "highly preferred" using email to communicate with HCPs about their combination regimens. However, HCPs felt that email was one of the least effective methods of communicating with patients. In focus groups, HCPs agreed that email is convenient when communicating about non-urgent matters. However, they were concerned that some patients may use email to communicate about urgent issues. Treatment-related AEs: When patients experienced treatment-related AEs, 30.1% said their clinicians tried a dose modification or hold. HCPs had mixed perceptions regarding the effectiveness of dose holidays. Those who felt this was highly effective included: advanced practice providers (42.9%), nurses (28.1%); oncologists (16.7%); and pharmacists (16.7%). Conclusions: This study identifies opportunities to improve care coordination for patients receiving combination IV/oral systemic anti-cancer regimens. These findings may inform the creation and dissemination of effective practices and quality improvement projects. These results may also help cancer programs tailor resources and incorporate proactive steps to address some of the key challenges patients may face.